1994
DOI: 10.7863/jum.1994.13.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography: not useful in detecting susceptibility to malignant hyperthermia.

Abstract: MH is a rare, potentially fatal complication of general anesthesia. Halothane‐caffeine contracture testing of a muscle biopsy is the only accepted diagnostic test for MH. A previous report indicated that ultrasonography may aid in diagnosis of MH. Using sonographic examination of the thigh and calf, we evaluated eight patients with proved susceptibility to MH and eight control patients. Two radiologists independently evaluated the sonograms for echogenicity and definition of fascial planes. We detected no cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Previous studies on muscle ultrasound in MH susceptible individuals have reported mixed results. Increased echogenicity in muscles of the lower extremities has been reported using a qualitative approach [ 43 ], however, this could not be reproduced [ 44 ]. Nevertheless, both studies were designed to study the usefulness of muscle ultrasound as a non-invasive test to diagnose MH susceptibility and did not use a quantitative analysis, a broad screening protocol, nor take neuromuscular symptoms into account.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on muscle ultrasound in MH susceptible individuals have reported mixed results. Increased echogenicity in muscles of the lower extremities has been reported using a qualitative approach [ 43 ], however, this could not be reproduced [ 44 ]. Nevertheless, both studies were designed to study the usefulness of muscle ultrasound as a non-invasive test to diagnose MH susceptibility and did not use a quantitative analysis, a broad screening protocol, nor take neuromuscular symptoms into account.…”
Section: Discussionmentioning
confidence: 99%
“…A heterogeneous and grainy pattern of the muscles, with a hypoechoic pattern of the septa and fascia is described by some [3], not by others [4]. The rarity of this syndrome in our ICU has until now prevented us from making an opinion.…”
Section: Malignant Hyperthermiamentioning
confidence: 95%